Synthesis of 5-(2-thienyl)-4,5-dihydrofurans and 7(2-thienyl)-2,8-dioxabicyc10[3.3.0]oct 3-enes using manganese(III)-based cyc1ization - Huỳnh, Thanh Trúc (Trường Đại học Đà Lạt, 2014)
l-Aryl-l-(2-thienyl)ethenes react with 2,4-pentanedione or ethyl acetoacetate in boiling acetic acid under the presence ofmanganese triacetate dihydrate affording new 4,5-dihydrofurans bearing a thienyl ring at the 5 position. On the other hand, these ethenes react with 3-acetyl-l-phenylpentane-l,4-dione in a similar reaction leading to theformation of7-(2-thienyl)-2,8 dioxabicyclo[3.3.0Joct-3-enes in high yields. The cis manner offused bicyclic products is briefly discussed.